Connecting with culturally diverse others - the case of Malaysian students’ social interactions on campus - Dalib, Syarizan (Immigrant Institute, Sweden, 2019)
Connecting with culturally diverse individuals require in-depth understanding and knowledge of intercultural competence. This paper focuses on the Malaysian students’ intercultural competence in the Malaysian campus to gain insights into their social interaction. Specifically, we highlight the Malaysian students’ reflection of intercultural competence based on their encounters with the international students in the Malaysian university environment. Using a qualitative approach, we collect data from in-depth interviews with the selected Malaysian undergraduate students from three universities in Northern Malaysia. The findings draw attention to two emerging themes: self-other awareness and inter-lingual communication strategies. The paper contributes to enhancing awareness of self and other, and language-related accommodation strategies in embracing intercultural communication.